2015
DOI: 10.1103/physreva.91.063402
|View full text |Cite
|
Sign up to set email alerts
|

Traces in ion yields and electron spectra of the formation of Ar inner-shell hollow states by free-electron lasers

Abstract: We explore the formation by Free-Electron-Laser radiation of Ar hollow states with two or three inner-shell holes. We find that even charged Ar ion states can be more populated than odd charged Ar ion states. This depends on the pulse intensity and the number of energetically accessible innershell holes. Fully accounting for fine structure, we demonstrate that one electron spectra bare the imprints of Ar hollow states with two inner-shell holes. Moreover, we show how the Auger spectra of these hollow states ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…In addition, using the method we developed in ref. 10 we compute the Auger rates for all allowed atomic transitions while we obtain the atomic single-photon ionization cross sections from ref. 47.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, using the method we developed in ref. 10 we compute the Auger rates for all allowed atomic transitions while we obtain the atomic single-photon ionization cross sections from ref. 47.…”
Section: Resultsmentioning
confidence: 99%
“…There has been a significant amount of work on calculating the Auger rates and photo-ionization cross sections in atoms [9][10][11][12][13][14] and molecules. [15][16][17][18][19][20][21] Computing these rates for molecules is more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…It applies to complex multi-electron atoms with bound orbital wave functions that can be accurately described when accounting for several angular momentum l quantum numbers. In contrast, the previous formalism we employed for computing single-photon ionisation cross sections and Auger rates for argon [22,23] and the formalism employed in the XATOM-model [24] use bound orbital wave functions described by only one l quantum number. Thus, the current formalism, allows for a more accurate computation of the single-photon ionization cross sections and Auger rates in the non-relativistic regime.…”
Section: Introductionmentioning
confidence: 99%
“…Although many researches on SCH and DCH states have been carried out in the past decades, however, very few studies are reported in the literature on the production of triple-core-hole (TCH) states 30 32 . Wallis et al .…”
Section: Introductionmentioning
confidence: 99%
“…Wallis et al . 30 theoretically studied the formation of TCH states in the 2p shell of an argon atom interacting with a free electron laser pulse. Carravetta et al .…”
Section: Introductionmentioning
confidence: 99%